Locomotive Game Model Training for Early Childhood - Asri, Novri; Siregar, Nofi Marlina; Sari, Eka Fitra Novita; Ali, Masnur (International Journal of Public Devotion, 2025)
Early childhood is a critical period for developing motor skills, especially locomotor movements such as walking, running, and jumping. However, many parents and educators lack adequate understanding and skills to apply effective and engaging play models that support optimal motor development. This community service activity aimed to provide training for parents and educators on implementing locomotor movement play models that are enjoyable, educational, and developmentally appropriate for young children. The activity was conducted at SD Negeri 1 Kamasan, Serang–Banten, through a combination of socialization sessions, practical training, and guided play simulations involving the children. Evaluation results showed a significant increase in participants’ knowledge, with average scores rising from 60.4 (pretest) to 86.6 (posttest), and the majority of participants classified in the high improvement category. Moreover, children’s motor skills improved by an average of 41.7%, particularly in jumping and coordination abilities. These findings indicate that locomotor play models are effective in enhancing the physical development of early childhood and can serve as a strategic approach integrated into early childhood education environments. The training also successfully raised awareness among parents and educators regarding the importance of physical activity as an essential component of holistic child development.Pelatihan Model Permainan Gerak Lokomotor untuk Anak Usia DiniABSTRAKMasa usia dini merupakan fase krusial dalam perkembangan keterampilan motorik anak, khususnya keterampilan gerak lokomotor seperti berjalan, berlari dan melompat. Sayangnya, banyak orang tua dan pendidik belum memiliki pemahaman serta keterampilan yang memadai dalam menerapkan model permainan yang dapat mengoptimalkan perkembangan motorik anak. Kegiatan Pengabdian kepada Masyarakat ini bertujuan untuk memberikan pelatihan kepada orang tua dan pendidik tentang penerapan model permainan gerak lokomotor yang menyenangkan, edukatif, dan sesuai dengan karakteristik anak usia dini. Kegiatan ini dilaksanakan di SD Negeri 1 Kamasan, Serang–Banten, melalui metode sosialisasi, pelatihan praktik, dan simulasi permainan bersama anak-anak. Hasil evaluasi menunjukkan peningkatan skor pengetahuan peserta dari rata-rata pretest 60,4 menjadi rata-rata posttest 86,6, dengan mayoritas peserta menunjukkan peningkatan signifikan dalam kategori tinggi. Sementara itu, kemampuan motorik anak mengalami peningkatan rata-rata sebesar 41,7%, terutama pada aspek melompat dan koordinasi gerak. Temuan ini menunjukkan bahwa model permainan gerak lokomotor efektif dalam mendukung perkembangan motorik anak usia dini, serta dapat menjadi pendekatan strategis yang dapat diintegrasikan dalam lingkungan pendidikan anak usia dini. Pelatihan ini juga meningkatkan kesadaran orang tua dan pendidik tentang pentingnya aktivitas fisik sebagai bagian integral dari pendidikan anak secara holistik.Kata Kunci:Anak usia dini; Gerak lokomotor; Keterampilan motorik